Comparative Situation Analysis of Childhood Asthma Incidence in Selected Hospitals Inside and Outside Dhaka City (Bangladesh Pharmaceutical Journal, 2020)
Asthma is a common chronic and long-term condition accompanied by coughing, wheezing, chest tightness and breathlessness and affects mainly the lungs. This study was aimed to explore the prevailing situation of asthma among the paediatric patients and its management inside and outside Dhaka city. The study was conducted on 420 asthma patients inside (n = 210) and outside (n = 210) Dhaka. Data were collected using a structured questionnaire from patients or their parents, during the period of January 2015 to June 2015. Most of the patients inside Dhaka reported that their children had frequent asthma attack than outside Dhaka (p